SISTEM MANAJEMEN PERSEDIAAN TERPADU UNTUK MENDUKUNG PENGEMBANGAN PRODUK UMKM PADA PARIWISATA BERKELANJUTAN DI DESA WISATA WATES JAYA, KABUPATEN BOGOR - Muliani, Lila; Suprayitno, Degdo; Hidayat, Yusup Rachmat (JURNAL ILMIAH EDUNOMIKA, 2024)
The issues faced by Small and Medium Enterprises (SMEs) in tourism villages, particularly regarding efficiency and effectiveness in the production process, remain an under-researched area. Most studies focus more on the development of tourism attractions and accommodations. However, within the 3S tourism concept (something to see, something to do, something to buy), the aspect of "something to buy" also deserves attention. This study aims to analyze the challenges and opportunities of utilizing technology to support product development for SMEs in Desa Wisata Wates Jaya, as well as to explore appropriate strategies for implementing technology in SME operations. Preliminary research has revealed that, in addition to capital issues, the workforce driving the SMEs in Wates Jaya Village lacks motivation in production. Problems related to calculating the cost of goods sold (COGS), forecasting raw material needs, and manual and disorganized bookkeeping/administrative processes have been identified as key concerns. This study adopts a qualitative approach using a case study of SMEs in Desa Wisata Wates Jaya. Data collection techniques include interviews, observation, and documentation. The findings show that SMEs in Wates Jaya Tourism Village already have a "local champion" who acts as a driving force, serving as a mediator, facilitator, and mobilizer. Support from village officials also strengthens the development of SMEs in the area. However, the lack of trained human resources, particularly in administrative tasks, and the underutilization of technology are notable weaknesses that hinder progress. An integrated system is expected to reduce minor errors through automation, which could also assist with administrative tasks, allowing SMEs in Desa Wisata Wates Jaya to become more resilient and thrive in the future